In situ encapsulation of Pd crystals inside foam-like carbon films continuously filled with α-Fe: investigating the nucleation of FePd3 alloys. Issue 59 (6th June 2016) - Boi, Filippo S.; Guo, Jian; Lan, Mu; Xiang, Gang; He, Yi; Wang, Shanling; Chen, Hongmei
Abstract : A key challenge in the fabrication and encapsulation of FePd alloys inside carbon materials is the achievement of continuous Fe x Pd x filling rates. Abstract : A key challenge in the fabrication and encapsulation of FePd alloys inside carbon materials is the achievement of continuous Fe x Pd x filling rates. We propose an advanced approach which allows the encapsulation of Pd crystals into foam-like carbon films continuously filled with α-Fe and the subsequent nucleation of the FePd3 alloys. The alloying-mechanism is also investigated.